2018
DOI: 10.1111/jocd.12851
|View full text |Cite
|
Sign up to set email alerts
|

Sterol‐standardized phytopharmaceutical from ground cherry: Corticoid‐like properties on human keratinocytes and fibroblasts and its effects in a randomized double‐blind placebo‐controlled clinical trial

Abstract: Background: Topical corticosteroids have been the most commonly prescribed drugs to treat skin inflammation, but their uses can lead to several adverse effects. Nowadays, new pharmacological strategies have been evaluated to improve dermatologic efficacy and reduce adverse effects, including natural products. Objectives:The aim of this study was to evaluate and compare the effects of a plant sterol standardized supercritical CO 2 phytopharmaceutical of Physalis angulata L. with hydrocortisone on the immune and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Topically applied Physalis angulata is also reported as a new and innovative phytopharmaceutical with various pharmacological effects that are potentially useful to protect human skin, especially against inflammation. (14) Another study also showed that PA cream containing physalin-E conferred benefits as an anti-inflammatory agent in acute and chronic dermatitis in experimental animals, which has therapeutic potential for the chronic and recurrent inflammatory disease AD. (15) Our study might give suggestions about whether Physalis angulata is a potential antiinflammatory drug.…”
Section: Introductionmentioning
confidence: 99%
“…Topically applied Physalis angulata is also reported as a new and innovative phytopharmaceutical with various pharmacological effects that are potentially useful to protect human skin, especially against inflammation. (14) Another study also showed that PA cream containing physalin-E conferred benefits as an anti-inflammatory agent in acute and chronic dermatitis in experimental animals, which has therapeutic potential for the chronic and recurrent inflammatory disease AD. (15) Our study might give suggestions about whether Physalis angulata is a potential antiinflammatory drug.…”
Section: Introductionmentioning
confidence: 99%